SQ4R METHOD AND READING COMPREHENSION DEVELOPMENT AMONG THE SOPHOMORE BUSINESS STUDNETS - Nelson Panjaitan; Rachel Palandeng (Fakultas Keguruan dan Ilmu Pendidikan Universitas Advent Indonesia, 2011)
This paper is an experimental study that involves the SophomoreEnglish students’ of Business Department of Adventist University of IndonesiaBandung was the subject of the research.The purposes of this study is to find whether there is a significant improvementby using SQ4R method on the Business students, and to describe the advantages andthe weakness of the SQ4R method based on research result.The people who have used the SQ4R method said that SQ4R is one of the simpleways in reading comprehension, because by using this method they could spend theirtime more efficiently to grasp and storage the main ideas easily.The researcher uses the pre-test and the post-test as the instrument. And the datais analyzed by using the T-test in computer.The result shows that tcounted = 2.5 > ttable 1.96 with significant level 0.025and the degree of freedom is 30 (df = N1+N2-2). This result means that the SQ4Rmethod is significantly improved the students reading comprehension.